#### Answer

4, 12

#### Work Step by Step

We square both sides of the equation and solve. Thus:
$ \sqrt{2n+1} = 2 + \sqrt{n-3} \\ 2n+1 = 4 + n -3 + 4\sqrt{n-3} \\ n = 4 \sqrt{n-3} \\ n^2 = 16(n-3) \\ n^2 - 16n + 48 = 0 \\ (n-4)(n-12) \\ n = 4, 12$

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

4, 12

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.